2013
DOI: 10.1002/rcm.6522
|View full text |Cite
|
Sign up to set email alerts
|

Single electron redox via an ion‐neutral complex in the fragmentation of protonated benzoylferrocenes

Abstract: The single electron redox reaction by the [substituted benzoyl/ferrocene] complexes was proposed by CID MS and theoretical calculations, which provided potential evidence to further understand the reversible reduction characteristics of ferrocene-containing biomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Already applied in other kinds of extractions, such as liquid phase microextraction [86], solid phase microextraction [87], liquid-liquid extraction [88], microwave assisted extraction [89] ultrasound-assisted extraction [90] or, as already mentioned, supercritical fluid extraction [30], ILs present some characteristics that make them potentially applicable in PLE, such as high solvent power, high chemical and thermal stability, non-flammability and non-volatility [91]. In this sense, Wu et al [92] already demonstrated the usefulness of pressurized ILs to extract flavonoids from F. sophorae Inmaturus herb.…”
Section: Methodological and Technological Advancesmentioning
confidence: 99%
“…Already applied in other kinds of extractions, such as liquid phase microextraction [86], solid phase microextraction [87], liquid-liquid extraction [88], microwave assisted extraction [89] ultrasound-assisted extraction [90] or, as already mentioned, supercritical fluid extraction [30], ILs present some characteristics that make them potentially applicable in PLE, such as high solvent power, high chemical and thermal stability, non-flammability and non-volatility [91]. In this sense, Wu et al [92] already demonstrated the usefulness of pressurized ILs to extract flavonoids from F. sophorae Inmaturus herb.…”
Section: Methodological and Technological Advancesmentioning
confidence: 99%
“…An ion‐neutral complex (INC) consists of an ionic fragment and a neutral molecule held together by electrostatic attraction instead of a normal covalent bond, which extensively exists as an intermediate in gas‐phase ionic reactions . Based on previous studies, one of the most important features of a true INC is that the two partners are able to rotate freely around one another, which permits reactions to occur at positions that are remote from the bond that is cleaved initially.…”
Section: Resultsmentioning
confidence: 99%
“…An ion-neutral complex (INC) consists of an ionic fragment and a neutral molecule held together by electrostatic attraction instead of a normal covalent bond, which extensively exists as an intermediate in gas-phase ionic reactions. [21][22][23] Based on previous studies, [24,25] one of the most important features of a true INC is that the two partners are able to rotate freely around one another, which permits reactions to occur at positions that are remote from the bond that is cleaved initially. As described in Scheme 1, rotation and a subsequent proton transfer between the two components within the complex INC-1 led to the protonbound complex of d and e, while direct separation of the complex INC-1 resulted in the product ion a.…”
Section: Proton Competitive Reaction By a Proton-bound Complexmentioning
confidence: 99%
“…In recent years, it has been demonstrated that the fragmentation of protonated ions involves ion‐neutral complexes as intermediates . In some cases, subsequent proton transfers between the ionic and neutral partners within the ion‐neutral complex result in a proton‐bound dimeric complex .…”
Section: Structures Of the Compounds Studiedmentioning
confidence: 99%